2022
DOI: 10.3389/fpsyg.2022.983930
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of influential factors developing the intention to use social media sites: A technology acceptance model based approach

Abstract: The aim of this study is to elaborate the different factors which attract users to use social media sites. These main factors are subjective norms, image, efficiency and satisfaction along with the mediating role of perceived usefulness. Survey method was used to collect data from B2B fashion brands in Pakistan. Convenient sampling technique was used to collect data from targeted respondents. Collected data was analyzed using Smart-PLS 3.3 version. Results express that subjective norms, image, efficiency and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown the possible effects of technology adoption on its users [52,68,87,96]. These results were consistent with the findings of the study (Hypothesis 9;10;11;12).…”
Section: -3-induction Stove Program Acceptance Toward Community Satis...supporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have shown the possible effects of technology adoption on its users [52,68,87,96]. These results were consistent with the findings of the study (Hypothesis 9;10;11;12).…”
Section: -3-induction Stove Program Acceptance Toward Community Satis...supporting
confidence: 92%
“…TAM is continuously updated and modified to incorporate new variables and contemporary applications of technology based on the respective study objectives. These applications include social media [52], agricultural sensor technology [53], autonomous and battery electric vehicles [54], electric vehicle charging [55,56], mobile learning technology [57], intelligent information technology [58], electric vehicles [46,59], digital transformation in hospitals [60], and virtual reality [47].…”
Section: -3-technology Readiness and Acceptancementioning
confidence: 99%